Building science and the physics of building enclosure performance - Keegan, Jennifer; Lemieux, Daniel J. (Selected technical papers, 2020)
"This compilation of Selected Technical Papers, STP1617, Building Science and the Physics of Building Enclosure Performance, contains peer-reviewed papers that were presented at symposiums held October 21-22, 2018, and December 2, 2018, in Washington, DC, USA. The symposiums were sponsored by ASTM International Committee E06 on Performance of Buildings and Committee D08 on Roofing and Waterproofing"--